Historical development of root analogue implants: a review of published papers. Issue 6 (July 2019) - Saeidi Pour, R.; Freitas Rafael, C.; Engler, M.L.P.D.; Edelhoff, D.; Klaus, G.; Prandtner, O.; Berthold, M.; Liebermann, A.
Abstract: The timetable for placing a dental implant can be crucial in the reduction of resorption of the socket after an extraction. The association of immediate implantation with an implant that copies the anatomy of the extracted root seems to add benefits in limiting the hard and soft tissue changes that may occur. The purpose of this paper is to provide an overview of the historical development of all types of root analogue implants from their beginning to the present day. To our knowledge the first individualised ones were described in 1969. Later, the use of titanium instead of the polymers that were used to start with offered better bony integration, and showed that the selection of materials was a key factor in their success. Root analogue implants made from zirconia were also described when attempts were being made to improve aesthetics in the anterior regions. The more recent introduction of digital technology such as DICOM has allowed the fabrication of these implants in less time, and the combination with digital diagnostic options such as cone-beam computed tomography facilitated the fabrication of some types of implants before extraction that could be inserted immediately into the alveolar socket with optimal and safe 3-dimensional positioning. Currently digital planning allows the clinician to design the ideal implant and abutment, which reduces the need for tissue grafting in the surgical phase and gingival conditioning in the prosthetic phase.